Psycho Peace Education? Bibliometric Analysis and Research Opportunity in Post-Conflict Areas - Mufti Riyani; Wasino Wasino; Suyahmo Suyahmo; Nugroho Trisnu Brata (Universitas Negeri Semarang, 2021)
Efforts to handle psychological through the utilization of educational institutions in post-conflict areas have not been made much. This paper aims to show opportunities for research with peace education based on the condition of social psychology in post-conflict society through bibliometric analysis. The method used in this study uses three software consisting of Publish or perish that functioned as a data-mining program, Mendeley as a reference manager, and VOSviewer to process the initial data into density mapping. The results showed that the opportunity to do this research is still very open. Three keywords consisting education, psycho social, and post-conflict as a fundamental concept offer positive connectedness and great opportunities to be followed up in field research. The conclusion of this study indicates that psycho peace education has the chance to become a new concept developed by activating educational institutions in post-conflict areas to handle psycho-social impacts. The formulation of a model of peace education can be extended by utilizing the principles of psycho-education to produce knowledge, skills, values, and attitudes that support peace.